Drug Dosing Considerations in Critically Ill Patients Receiving Continuous Renal Replacement Therapy - Soo Min Jang; Sergio Infante; Amir Abdi Pour (MDPI AG, 2020)
Acute kidney injury is very common in critically ill patients requiring renal replacement therapy. Despite the advancement in medicine, the mortality rate from septic shock can be as high as 60%. This manuscript describes drug-dosing considerations and challenges for clinicians. For instance, drugs’ pharmacokinetic changes (e.g., decreased protein binding and increased volume of distribution) and drug property changes in critical illness affecting solute or drug clearance during renal replacement therapy. Moreover, different types of renal replacement therapy (intermittent hemodialysis, prolonged intermittent renal replacement therapy or sustained low-efficiency dialysis, and continuous renal replacement therapy) are discussed to describe how to optimize the drug administration strategies. With updated literature, pharmacodynamic targets and empirical dosing recommendations for commonly used antibiotics in critically ill patients receiving continuous renal replacement therapy are outlined. It is vital to utilize local epidemiology and resistance patterns to select appropriate antibiotics to optimize clinical outcomes. Therapeutic drug monitoring should be used, when possible. This review should be used as a guide to develop a patient-specific antibiotic therapy plan.